On Carlitz theorem for Bernoulli polynomials - Bartz, Krystyna M. (Annales Mathematicae Silesianae, 1998)
The well-known Carlitz theorem for the Bernoulli numbers Bn, (see [3]) is extended to the case of values of the Bernoulli polynomials Bn(y) at rational points a/b, where (b,n!) = 1.